Escrituras de lo cercano. Apuntes para una teoría de la historia reciente argentina - Florencia Levín (Nuevo mundo - Mundos Nuevos, 2017)
Regarding the shock caused by the Holocaust, and in the light of the deep transformations of the ways of experimenting and measuring time, along the last thirty-five years new historiographies have arisen in European and Latin-American countries that focus on a nearby temporality. With the aim to contribute to the wide theoretical and historiographical map of these new disciplines, as well as to contribute to the theoretical construction of the field in Argentina, in this text I propose to explore its disciplinary foundations in the social experience of state terrorism.